Peculiar spline collocation method for solving rough and stiff delay differential problems - F. Calio; E. Marchetti; R. Pavani (Journal of Numerical Analysis and Approximation Theory, 2004)
As well known, solutions of delay differential equations (DDEs) are characterized by low regularity. In particular solutions of neutral delay differential equations (NDDEs) frequently exhibit discontinuities in the first derivative so that the differential problems become rough. The aim of this paper is to approximate the solutions of such rough delay differential problems by means of a peculiar deficient spline collocation method. Significant numerical examples are provided to enlighten the features of the proposed method.